Smallholder Coffee Productivity as Affected by Socioeconomic Factors and Technology Adoption - Wambua, Daniel M.; Gichimu, Bernard M.; Ndirangu, Samuel N. (Hindawi, 2021)
Despite the increase in area under coffee in Kenya in the last decade, productivity has been on the decline. Numerous production technologies have been developed through on-station research but there has been limited on-farm research to assess the impact of these technologies at the farm level. On the other hand, smallholder farmers are endowed differently and this would positively or negatively affect the adoption of recommended technologies and hence coffee productivity. -is study was carried out to evaluate the effects of socioeconomic factors and technology adoption on smallholder coffee productivity at the farm level. -e study employed stratified random sampling where 376 farmers were randomly sampled from six cooperative societies which had been preselected using probability proportional to the size sampling technique. -e effects of socioeconomic factors and technology adoption on coffee productivity were analyzed using the stochastic Cobb-Douglas production function. -e study revealed that off-farm income, access to credit, type of land tenure, and land size had significant positive effects on coffee productivity. -erefore, coffee farmers should be encouraged to diversify their income sources and to embrace credit financing, as the government reviews land use policies to avail adequate agricultural land. -e study further revealed that the adoption of recommended application rates of manure, fungicides, and pesticides had significant positive effects on coffee productivity. -e adoption of these technologies should therefore be enhanced among small-scale farmers to improve coffee productivity at the farm level.